The Cladistic Technique for Territorial Studies - Giovanni Rabino; Francesco Scarlatti (European Regional Science Association (ERSA), 2003)
The cladistic is an technique born in the field of biology. Starting from the physics characteristics of some elements, the cladistic method try to find the hierarchical links between them in the bases of their similarity and of the research of “evidences” of relationship. The goal of this paper is to verify the potentialities of this method in the studies of the territory, in order to find correlation among different spatial areas. Considering social, economic, environmental indicators that characterise the areas of a given territory, we analyse the links between different areas, organising these links according to a hierarchical tree. The result is then compared with ones obtained using more traditional methods as multicriterial analysis, statistics and clustering.
Keywords: 330